Autoimmune Theories of Chronic Spontaneous Urticaria - Bracken, Sonali J.; Abraham, Soman; MacLeod, Amanda S. (Frontiers in Immunology, 2019)
Urticaria (hives) is a highly prevalent skin disorder that can occur with or without associated angioedema. Chronic spontaneous urticaria (CSU) is a condition which persists for more than six weeks in duration and occurs in the absence of an identifiable provoking factor. CSU results from pathogenic activation of mast cells and basophils, which gives rise to the release of proinflammatory mediators that support the generation of urticaria. Several theories have been put forth regarding the pathogenesis of CSU with much evidence pointing towards a potential autoimmune etiology for this condition in up to 50% of patients with this condition. In this review, we highlight the evidence surrounding the autoimmune pathogenesis of chronic urticaria including recent data which suggests that CSU may involve contributions from both immunoglobin G (IgG)-specific and immunoglobulin E (IgE)-specific autoantibodies against a vast array of antigens that can span beyond those found on the surface of mast cells and basophils.